2011
DOI: 10.1007/s11302-011-9226-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological significance of P2X receptor-mediated vasoconstriction in five different types of arteries in rats

Abstract: P2X 1 receptors, the major subtype of P2X receptors in the vascular smooth muscle, are essential for α,β-methylene adenosine 5′-triphosphate (α,β-MeATP)-induced vasoconstriction. However, relative physiological significance of P2X 1 receptor-regulated vasoconstriction in the different types of arteries in the rat is not clear as compared with α 1 -adrenoceptor-regulated vasoconstriction. In the present study, we found that vasoconstrictive responses to noncumulative administration of α,β-MeATP in the rat isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Our recent study demonstrated that the maximal vasoconstriction mediated by P2X 1 receptors reached at least 40% of those mediated by α 1 -adrenoceptors in the rat internal carotid, mesenteric and pulmonary arteries. P2X 1 receptormediated vasoconstriction even reached 80% in the caudal artery [24] , which suggested that purinergic transmission can be useful to maintain the basal vascular tone and could be important to the hemodynamic control in rats subjected to exhaustive swimming exercise. Sugawara et al [41] also suggested that a reduction in α-adrenoceptor-mediated vascular tone contributes to improved arterial compliance in healthy adults who engage in endurance exercise.…”
Section: Wwwnaturecom/aps LI L Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent study demonstrated that the maximal vasoconstriction mediated by P2X 1 receptors reached at least 40% of those mediated by α 1 -adrenoceptors in the rat internal carotid, mesenteric and pulmonary arteries. P2X 1 receptormediated vasoconstriction even reached 80% in the caudal artery [24] , which suggested that purinergic transmission can be useful to maintain the basal vascular tone and could be important to the hemodynamic control in rats subjected to exhaustive swimming exercise. Sugawara et al [41] also suggested that a reduction in α-adrenoceptor-mediated vascular tone contributes to improved arterial compliance in healthy adults who engage in endurance exercise.…”
Section: Wwwnaturecom/aps LI L Et Almentioning
confidence: 99%
“…A ring segment (4 mm long) without endothelium was mounted horizontally in a 10-mL organ bath, and the isometric tension was recorded by a polygraph (ERT-884, Youlin Electron Co, Kaifeng, China). Preloads were applied to the preparations of internal carotid artery (1.0 g), caudal artery (0.75 g), pulmonary artery (1.0 g), mesenteric artery (1.0 g), and aorta (2.0 g) [24] . The preparations were allowed to equilibrate for 1 h in K-H solution.…”
Section: Arterial Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A ring segment (4 mm long) without the endo-www.chinaphar.com Zhao J et al Acta Pharmacologica Sinica npg thelium was mounted horizontally in a 10-mL organ bath by carefully inserting a tungsten wire through the lumen of the arterial ring preparation and anchoring it to a stationary support. Another similarly inserted tungsten wire was connected to an isometric tension transducer coupled to a polygraph (ERT-884, Youlin Electron Co, Kaifeng, China) [19] to record the change in tension of the preparation. A preload of 0.75 g was applied to the arterial ring preparations, and the preparations were allowed to equilibrate for 1 h in Krebs-Henseleit (K-H) solution with the following composition (mmol/L) [19,20] : NaCl 133, KCl 4.7, NaH 2 PO 4 1.35, NaHCO 3 16.3, MgSO 4 0.61, glucose 7.8, and CaCl 2 2.52 with a pH 7.4.…”
Section: Isolated Caudal Arterymentioning
confidence: 99%
“…Another similarly inserted tungsten wire was connected to an isometric tension transducer coupled to a polygraph (ERT-884, Youlin Electron Co, Kaifeng, China) [19] to record the change in tension of the preparation. A preload of 0.75 g was applied to the arterial ring preparations, and the preparations were allowed to equilibrate for 1 h in Krebs-Henseleit (K-H) solution with the following composition (mmol/L) [19,20] : NaCl 133, KCl 4.7, NaH 2 PO 4 1.35, NaHCO 3 16.3, MgSO 4 0.61, glucose 7.8, and CaCl 2 2.52 with a pH 7.4. The K-H solution was maintained at 37 °C and aerated with 95% O 2 and 5% CO 2 .…”
Section: Isolated Caudal Arterymentioning
confidence: 99%